Time for change: compliance with RCS green theatre checklist—facilitators and barriers on the journey to net zero - Westwood, Elizabeth; Walshaw, Josephine; Boag, Katie; Chua, WeiYing; Dimashki, Safaa; Khalid, Hammaad; Lathan, Ross; Wellington, Jack; Lockwood, Sonia; Yiasemidou, Marina (Frontiers in Surgery, 2023)
Climate change is an era-defining health concern, with healthcare related emissions paradoxically compounding negative impacts. The NHS produces 5% of the UK's carbon footprint, with operating theatres a recognised carbon hotspot. NHS England aims to become Net Zero by 2045. Consequently, UK Royal Colleges of Surgery have published guidance to foster an evidence-based sustainable transformation in surgical practice.A single-centre quality improvement project was undertaken, aiming to provide an overview of sustainable practice locally. The Intercollegiate "Green Theatre Checklist" was taken as an audit standard, focusing on "preparing for surgery" and "intraoperative equipment" subsections. Any general surgical procedure was eligible for inclusion. Usage of reusable textiles, non-sterile gloves, catheters, antibiotics, alcohol vs water-based scrub techniques, skin sterilisation choices, and skin closure materials were recorded. Baseline data collection occurred over a 3 week period, followed by dissemination of results locally via clinical governance meetings and poster displays. A re-audit of practice was conducted using the same methodology and duration.Datasets 1 (n=23) and 2 (n=23) included open (n=22), laparoscopic (n=24), elective (n=17) and non-elective (n=29) cases. Good practice was demonstrated in reusable textiles (trolley covers 96%, 78%, drapes 100%, 92%) however procurement issues reduced otherwise good reusable gown use in Dataset 2 in (90%, 46%). No unnecessary catheter use was identified, and loose skin preparations were used unanimously. Uptake of alcohol-based scrubbing techniques was low (15%, 17%) and unnecessary non-sterile glove use was observed in >30% of procedures. All laparoscopic ports and scissors were single use. Carbon footprints were 128.27 kgCO2e and 117.71 kgCO2e in datasets 1 and 2 respectively.This project evidences good practice alongside future local focus areas for improved sustainability. Adoption of hybrid laparoscopic instruments, avoiding unnecessary equipment opening, and standardising reusable materials could reduce carbon and environmental impact considerably. Successful implementation requires considered procurement practices, improved awareness and education, clear leadership, and a sustained cultural shift within the healthcare community. Collaboration among professional institutions and access to supporting evidence is crucial in driving engagement and empowering clinicians to make locally relevant changes a reality.